MEMAHAMI PROSES MARKETISASI LEMBAGA PENYIARAN PUBLIK UNTUK MEMPERTAHANKAN EKSISTENSI DI ERA DIGITAL: STUDI KASUS TVRI STASIUN JAWA TENGAH - Cathlene Tanty Rahmaika Tambunan Cathlene Tanty Rahmaika Tambunan; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The development of the digital era has shifted public media consumption patterns and threatened the existence of broadcasting media in Indonesia, including TVRI as a Public Service Broadcaster. As a public broadcasting institution, TVRI has been mandated to reach all Indonesian citizens under Government Regulation No. 13 of 2005. However, a decline in terrestrial television viewership and the failure to achieve the 2025 Non-Tax State Revenue (PNBP) target have been experienced by TVRI. These conditions have encouraged TVRI Central Java Station to integrate market logic into a non-commercial public institution, a process referred to as marketization. This study was conducted to understand the marketization process undertaken by TVRI Central Java Station in maintaining its existence in the digital era. A qualitative approach with a post-positivist paradigm was employed. Data were collected through in-depth interviews with eight informants, direct observation, and documentation, and were subsequently analyzed using a case study method based on Murschetz's (2017) Extended Structure–Conduct–Performance (SCP) framework. The findings indicate that changes in market structure and government policies have led TVRI Central Java Station to implement marketization through a hybrid institutional logic, in which market logic and public service logic are simultaneously applied. Market logic is manifested through direct marketing, audience segmentation, advertising product diversification, multiplatform distribution, the use of artificial intelligence (AI) to improve production efficiency, and the utilization of commercial opportunities. On the other hand, public service logic is maintained through the production of informational and local cultural content, international to local news programs delivered in regional languages, religious education programs, the application of news framing that prioritizes national unity, and the relay broadcasting of TVRI National and Presidential broadcasts. This study concludes that marketization at TVRI Central Java Station does not represent full commercialization but rather an institutional negotiation between market logic and the public service mandate. The existence of public service broadcasting institutions in the digital era is determined by their ability to build digital visibility while preserving their identity as public media institutions. Therefore, content strategies should be optimized according to the characteristics of each digital platform, human resource capacity should be strengthened, and a more accurate audience measurement system should be developed.